SAMUEL JOHNSON’S THOUGHTS ABOUT ISLAM - Hüseyin Çaksen (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
This review essay is about a late nineteenth-century book on Islam written by an American Orientalist Samuel Johnson (1822-1882). Johnson was a clergyman, a consecrated minister, a scholar of large attainments, an author, and by nature a poet. More especially, he was a student and interpreter of the Far Eastern religions. Whatever his work, he brought into it an open, cultivated, and philosophic mind. The most enduring monument to Johnson’s labour is his scholarly and philosophical study of the Oriental Religions: India (1872); China (1877); and Persia (1885). This study engaged him during his whole ministry and to the end of his life.